Analisis Respon Sistem Kendali LQR (Linear Quadratic Regulator) Pada Simulasi Gimbal Kamera Dua Sumbu - Qalisha Putri Syahna; Elvan Yuniarti; Edi Kurniawan (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2019)
Research has been conducted to analyzed the responses of the two axis camera gimbal control system for pitch and roll direction using the Linear Quadratic Regulator (LQR) control system. It focused on the effect from the value of gain Q in calculation of the LQR. The system output was plotted into a step signal so it will be analyzed with transient response method and plotted into sinusoidal signals to find the amplitude value along with the amplitude time. For comparison, the PID control system with the auto-tuning method was also used in this study. It has been done in order to find out whether the LQR control system is more appropriate to use in the two axis camera gimbal system or not. The result from the analysis of the variation of the Q value given at both angles is that the system runs stable when the value of P= 4 for roll angle and P= 6 for pitch angle. For the effect from value of gain Q on the whole system is it will make the output significally changed when the P=1-10. While the results of the comparison can prove that the LQR control system has a better system responses.